Legend : a harrowing story from the Vietnam War of one Green Beret's heroic mission to rescue a Special Forces team caught behind enemy lines - Blehm, Eric (New York : Crown Publishing, 2015)
The author takes as his canvas the Vietnam War, as seen through a single mission that occurred on May 2, 1968. A twelve-man Special Forces team had been covertly inserted into a small clearing in the jungle of neutral Cambodia--where U.S. forces were forbidden to operate. The team did not know they had infiltrated a section of jungle that concealed a major enemy base.
Street kid from Cuero -- "Look sharp, be sharp, go Army!" -- The darkest white -- Green Beret -- The secret war -- Anatomy of a mission -- Welcome to Detachment B-56 -- Over the fence -- The launch -- As bad as it gets -- Daniel Boone tactical emergency -- If someone needs help-- -- Last chance -- Deliverance -- Mettle for medal.
Includes index.
Keywords: Benavidez, Roy P; United States. -- Army. -- Special Forces -- History -- 20th century; Vietnam War, 1961-1975 -- Commando operations -- United States; Vietnam War, 1961-1975 -- Search and rescue operations -- Cambodia